Manajemen Risiko pada UMKM “Kedai Putri Tunggal” di Cimahi - Nurhandayani, Dini; Rahma Fadzillah, Kylla Almira; Amalia, Tanti (Universitas Serambi Mekkah, 2024)
This research focuses on the MSME Kedai Putri Tunggal which sells various kinds of children's snacks. As time goes by, the number of businesses run by the community is increasing, namely small businesses and medium businesses. MSME is an abbreviation for Enterprise, Micro, Small, Medium (Jesslyn at al., 2022). In other words, MSMEs are business entities that are practiced individually, households or small businesses. The existence of MSMEs is quite important in social life. Not only that, MSMEs also play an important role in the national economy (As Sajjad at al., 2020). With the existence of MSMEs, unemployment rates in Indonesia can be minimized by creating their own jobs (Suhartini, 2021). In carrying out business processes, of course there are risks that might hamper these business activities. Therefore, as MSMEs, you also need to know what risk management is. Risk management is needed to anticipate or reduce the possibility of risks occurring in a business. The research method used uses a descriptive analysis approach. What was obtained from an interview with UMKM